Improving Student’s Writing Skill Of Recount Text Through Diary Writing For Tenth Grade At Sma Swasta Kampus Nommensen Pematangsiantar - Hutahaean, Grace Saurma; Siahaan, Mungkap Mangapul; Sihombing, Partohap Saut Raja; Pasaribu, Sunggul (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine and describe students' difficulties in writing procedural texts in the tenth grade of SMA Swasta Kampus Nommensen Pematangsiantar and completion through diary media. This research method is designed as a quantitative research. The research chose students of grades X-2 and X-3 as the subjects of this research, consisting of 50 students. The technique used in collecting data was a writing test. The researcher chose alternative media to help students improve their recount text writing skills by using diaries. Upon examining the data, it was revealed that the cumulative score for the grammar test amounted to 1,246, resulting in a mean of 49.84. In contrast, the writing test yielded a total score of 1,610, with an average of 64.40. To The findings unveiled a robust connection between these two domains, with a correlation coefficient of 0.127, signifying a notably high correlation, as values ranging from 0.00 to 0.199 indicate a strong association.